Proposisi Pengelolaan Asesmen Hasil Belajar dalam Pengendalian Mutu Pendidikan - Idam Mustofa; Mohamad Mustafid Hamdi (Intizam, Jurnal Manajemen Pendidikan Islam, 2022)
The learning program should be modified in accordance with the characteristics of the students which stem from four aspects, namely cognitive, affective, and psychomotor as well as physiological aspects. However, the trend of quality control in education is mostly focused on developing quality assurance and ignoring the assessment of learning outcomes. In fact, to obtain information about student development as part of efforts to satisfy educational customers requires simultaneous assessments. To ensure the fulfillment of these things, a comprehensive assessment of development and learning outcomes is needed supported by a measurement system that is in accordance with the characteristics of students. This effort is carried out as information on the development and learning outcomes of students in order to ensure the quality of education and learning. Assessment of learning outcomes as quality control of education can be formulated by combining assessment and evaluation of programs that can be applied to the implementation of the curriculum by conducting research, both qualitative and quantitative